Defining comprehensive biomarker‐related testing and treatment practices for advanced non‐small‐cell lung cancer: Results of a survey of U.S. oncologists. (17th December 2021) - Mileham, Kathryn F.; Schenkel, Caroline; Bruinooge, Suanna S.; Freeman‐Daily, Janet; Basu Roy, Upal; Moore, Amy; Smith, Robert A.; Garrett‐Mayer, Elizabeth; Rosenthal, Lauren; Garon, Edward B.; Johnson, Bruce E.; Osarogiagbon, Raymond U.; et al.
Abstract: Background: An ASCO taskforce comprised of representatives of oncology clinicians, the American Cancer Society National Lung Cancer Roundtable (NLCRT), LUNGevity, the GO2 Foundation for Lung Cancer, and the ROS1 ders sought to: characterize U.S. oncologists' biomarker ordering and treatment practices for advanced non‐small‐cell lung cancer (NSCLC); ascertain barriers to biomarker testing; and understand the impact of delays on treatment decisions. Methods: We deployed a survey to 2374 ASCO members, targeting U.S. thoracic and general oncologists. Results: We analyzed 170 eligible responses. For non‐squamous NSCLC, 97% of respondents reported ordering tests for EGFR, ALK, ROS1, and BRAF . Testing for MET, RET, and NTRK was reported to be higher among academic versus community providers and higher among thoracic oncologists than generalists. Most respondents considered 1 (46%) or 2 weeks (52%) an acceptable turnaround time, yet 37% usually waited three or more weeks to receive results. Respondents who waited ≥3 weeks were more likely to defer treatment until results were reviewed (63%). Community and generalist respondents who waited ≥3 weeks were more likely to initiate non‐targeted treatment while awaiting results. Respondents <5 years out of training were more likely to cite their concerns about waiting for results as a reason for not ordering biomarker testing (42%, vs. 19% with ≥6 years of experience). Conclusions: Respondents reported high biomarker testing rates in patients with NSCLC. Treatment decisions were impacted by test turnaround time and associated with practice setting and physician specialization and experience. Abstract : U.S. oncologists who typically waited ≥3 weeks for biomarker test results were more likely to defer initiating treatment for patients with advanced non‐small‐cell lung cancer until results were reviewed. Treatment decision‐making based on biomarker test results was associated with practice setting and physician specialization and years of experience. Frequency that oncologist's concern about delaying treatment is a reason for not testing, by years since oncology training completed.